2008
DOI: 10.1111/j.1440-1843.2008.01315.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory markers in exhaled breath condensate from patients with asthma

Abstract: Measurement of EBC biomarkers is a non-invasive and useful way to evaluate airway inflammation in patients with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 34 publications
3
67
2
1
Order By: Relevance
“…Contrary to our results, other studies have reported total NO 2 -/NO 3 -level in EBC to be elevated in subjects with asthma compared to healthy nonsmoking subjects [17], healthy nonatopic controls [5] or controls [9]. These conflicting results may be due to the very small number of subjects included in these studies, the various methodologies used for measuring NO 2 -and NO 3 -levels, the choice of the reference group for comparisons and other differences such as those related to phenotypes definition.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our results, other studies have reported total NO 2 -/NO 3 -level in EBC to be elevated in subjects with asthma compared to healthy nonsmoking subjects [17], healthy nonatopic controls [5] or controls [9]. These conflicting results may be due to the very small number of subjects included in these studies, the various methodologies used for measuring NO 2 -and NO 3 -levels, the choice of the reference group for comparisons and other differences such as those related to phenotypes definition.…”
Section: Discussioncontrasting
confidence: 99%
“…Both epidemiological and clinical studies have shown increased level of FeNO in children and adults with asthma, and positive associations between FeNO and allergic sensitisation are consistent over the studies, regardless of rhinitis or asthma [4]. Studies on associations between NO 2 -and NO 3 -levels with asthma, allergy or rhinitis have led to more conflicting results both in adults and children [5][6][7][8][9][10][11][12][13][14][15][16][17]. Until now, none of these studies has simultaneously performed measurements of EBC NO 2 -/NO 3 -and FeNO levels in the same subjects.…”
Section: Introductionmentioning
confidence: 87%
“…In the study performed by Ueno et al [31], in which CRP was measured using ELISA with a high sensitivity, the authors demonstrated raised CRP levels in the EBC in asthmatics compared with healthy volunteers. These results were confirmed by our previous report, in which the increase in hs-CRP levels both in serum and EBC and the correlation of this parameter with F ENO and ECP in asthmatic patients were revealed [32].…”
Section: Discussionmentioning
confidence: 99%
“…Both H 2 O 2 and NO are associated with oxidative stress, which is defined as an imbalance between oxidants and antioxidants, and is thought to be involved in airway inflammation and respiratory diseases [47] H 2 O 2 is generated from superoxide anion by the action of superoxide dismutase in neutrophils, eosinophils, macrophages and epithelial cells, and in particular, by eosinophils in asthma [48][49][50] Exhaled nitric oxide (eNO) is a marker of airway inflammation [1]. Although NO is produced in the airways by a variety of cells, large amounts may be generated from those involved in the acute and chronic inflammatory responses [51].…”
Section: Article In Pressmentioning
confidence: 99%